PENGARUH AKUNTANSI KEBERLANJUTAN, TATA KELOLA DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Saraswati, Wiwik; Rama Pramudia, Dimas; Anam, Hairul (MEDIA RISET EKONOMI [MR.EKO], 2024)
This research aims to determine the influence of sustainability accounting, governance and capital intensity on tax avoidance. The research population is mining companies registered on the BEI for the period 2021 – 2023 with a total of 111 observations. Tax avoidance as the dependent variable is calculated using cash etr. The independent variable sustainability accounting is calculated by the number of standard GRI items reported by the company divided by the Standard Gri indicator, while corporate governance uses the ratio of managerial ownership which is measured by the number of shares owned by managers and Capital Intensity is measured using the company's total assets. The results of testing the sustainability accounting hypothesis have no effect on tax avoidance because the size of the funds spent and the large or small number of sustainability reports do not affect the size of the taxes paid, managerial ownership has an effect on tax avoidance, this is because the managerial side has an effect on the amount of taxes paid by the company, whereas Capital intensity influences tax avoidance because the size of a company's assets can influence the amount of tax paid.